Photoshop 7.0 upgrade essentials. - Loader, Vicki, ....-; Huggins, Barry, ....- (Birmingham : Friends of ED, 2002)
1.Photoshop 7.0 upgrade overview 2.The file browser and workspaces
Keywords: Beeldbewerking; Computer graphics; Photoshop; Webdesign